2008
DOI: 10.1038/mt.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis With Intramuscular NV1FGF Improves Amputation-free Survival in Patients With Critical Limb Ischemia

Abstract: This study evaluated the efficacy and safety of intramuscular administration of NV1FGF, a plasmid-based angiogenic gene delivery system for local expression of fibroblast growth factor 1 (FGF-1), versus placebo, in patients with critical limb ischemia (CLI). In a double-blind, randomized, placebo-controlled, European, multinational study, 125 patients in whom revascularization was not considered to be a suitable option, presenting with nonhealing ulcer(s), were randomized to receive eight intramuscular injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
163
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 295 publications
(175 citation statements)
references
References 25 publications
5
163
0
7
Order By: Relevance
“…The calculation of sample size for the combined event rate (amputation and death) was based on the TALISMAN PM201 study 16 in which a hazard ratio (HR) of 0·558 was recorded. With the assumption of a combined event rate (major amputation or death) at 1 year of at least 35% in the placebo group, a fi xed HR of 0·56, a fi xed patient follow-up of 12 months, and a drop-out rate of 5%, a sample size of 490 patients (245 patients in each treatment group) would give a minimum power of 90% to show a 44% reduction in events with NV1FGF compared with placebo, with a twosided log-rank test at a 5% signifi cance level.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculation of sample size for the combined event rate (amputation and death) was based on the TALISMAN PM201 study 16 in which a hazard ratio (HR) of 0·558 was recorded. With the assumption of a combined event rate (major amputation or death) at 1 year of at least 35% in the placebo group, a fi xed HR of 0·56, a fi xed patient follow-up of 12 months, and a drop-out rate of 5%, a sample size of 490 patients (245 patients in each treatment group) would give a minimum power of 90% to show a 44% reduction in events with NV1FGF compared with placebo, with a twosided log-rank test at a 5% signifi cance level.…”
Section: Resultsmentioning
confidence: 99%
“…15 In the phase 2 TALISMAN trial, 16 administration of NV1FGF (4 mg every 2 weeks) showed a similar improvement in ulcer healing (the primary endpoint) to that of placebo, but a 62·9% reduction of the risk of major amputation (p=0·015) and a 56% reduction of the risk of major amputation or death (p=0·009) at 12 months as compared with placebo.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…While repeated administration of the angiogenic gene may increase the chances of success as demonstrated by a recent study treating CLI patients with FGF-1 [5], the current thought is that use of a combination of growth factors, or "master switches" (e.g. hypoxia-inducible factor (HIF)-1α), may be better strategies for successful revascularization [6] due to the molecular complexity of angiogenesis and vasculogenesis.…”
Section: Current Treatment Options and Rationale For Cell-based Appromentioning
confidence: 99%